The Correlation between Budgets and Matriculation Exams: The Case of Jewish and Arab Schools in Israel - Rami Zeedan; Rachel Elizabeth Hogan (MDPI AG, 2022)
Standardized testing in the Israeli education system presents a cavernous achievement gap between the dominant Jewish and Arab student populaces. This paper assesses the role of one major factor contributing to this discrepancy in test scores: budget allocation. Specifically, we evaluate the relationship between test scores and budget in Israel proper while controlling for Arab and Jewish school systems. The findings from the 2008 to 2018 data demonstrate the increased allocation of budgets and higher test scores in Arab schools. The statistical analysis confirmed a positive correlation between budgets and test scores. Overall, budget factors were found to have a much higher impact on Arab schools than Jewish schools. This was even more significant in Druze schools, which received the higher increase in budget and achieved the most significant improvements in Bagrut scores. As a result, this research challenges previous findings within the educational literature, identifies significant implications as byproducts of this variable relationship, and proposes future policy adjustments and research expansion.